Prática de discussão coletiva de uma professora em Álgebra - Rodrigues, Cátia (2018)
This article presents a study that aims to describe and to understand the mathematical discussion practice of a teacher during the preparation and promotion of a collective discussion in Algebra with 7th grade students. The study follows a qualitative and interpretative approach and follows a case study design of a mathematics teacher. The results show that the teacher begins by carefully selects the task she intends to present to the students, anticipating possible strategies for resolving the problem, using algebraic language. In class, in the promotion of the discussion, he/she concretizes the preparation made leading the students to present their strategies of resolution, to compare and evaluate the colleagues, filtering the various contributions, so that the most relevant aspects of their work are synthesized. The teacher leads students to generalize and justify algebraic ideas, by combining intentional actions of eliciting, supporting, informing and challenging.